1984
DOI: 10.1002/jnr.490120224
|View full text |Cite
|
Sign up to set email alerts
|

The functional recovery of damaged brain: The effect of GM1 monosialoganglioside

Abstract: In the present study the topology and the biochemical mechanisms underlying the functional recovery of the dopaminergic nigrostriatal system is further analyzed. Rats with unilateral hemitransection were treated with 30 mg/kg GM1 monosialoganglioside or with its internal ester derivative for different periods of time. GM1 enhances 3H-dopamine uptake in striatal synaptosomes of the lesioned side, and the enhancement of dopamine uptake precedes that of striatal tyrosine hydroxylase activity. The above biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Although chronic G,, treatment has been shown to increase striatal dopamine levels after a number of different types of lesions (Toffano et al, 1984a), this effect seems to be dependent, to a large extent, on the severity of the lesion (Ramirez and Sabel, 1990). GM, was effective in partially restoring striatal dopamine levels and TH activity after partial unilateral hemi-transactions of the medial forebrain bundle, but had no effect on striatal neurochemistry in animals with almost complete lesions (Toffano et al. 1984b).…”
Section: Discussionmentioning
confidence: 90%
“…Although chronic G,, treatment has been shown to increase striatal dopamine levels after a number of different types of lesions (Toffano et al, 1984a), this effect seems to be dependent, to a large extent, on the severity of the lesion (Ramirez and Sabel, 1990). GM, was effective in partially restoring striatal dopamine levels and TH activity after partial unilateral hemi-transactions of the medial forebrain bundle, but had no effect on striatal neurochemistry in animals with almost complete lesions (Toffano et al. 1984b).…”
Section: Discussionmentioning
confidence: 90%
“…testing paradigms [Karpiak, 1983;Toffano et al, 1984; Based upon the evidence cited above, we propose Sabel et al, 1983Sabel et al, , 1984a. A possible explanation that an intact visual system may be necessary for brainof our present failure to replicate earlier data comes from damaged animals to benefit from some of the therapeutic work by Toffano et a1 [1984] that indicates an interaction effects of GMl ganglioside.…”
Section: Discussionmentioning
confidence: 62%
“…Their neuritogenic properties have been well documented [Byrne et al, 1983;Leon et al, 1982;Morgan and Seifert, 1979;Ryback et al, 19831. Research based on these findings indicates that exogenously administered gangliosides may act as neuronotropic agents, promoting structural and behavioral change following central nervous system trauma [Fass andRamirez, 1984 Karpiak, 1983;Toffano et al, 1984;Sabel et al, 1984a,b, 19851. Following this line of investigation, the aim of the present study was to determine if GMl ganglioside treatment can promote behavioral recovery following damage to a specific sensory system. In order to answer this question, we tested rats on both a brightness and a pattern discrimination task after bilateral ablation of the visual cortex subsequent to treatment with GM1 gangliosides or a control substance.…”
Section: Introductionmentioning
confidence: 99%
“…the monosialoganglioside GM1 (Fidia, Italy) were found to alleviate or prevent some of the behavioral deficits associated with a variety of central nervous system (CNS) lesions (Skaper et al 1989;Toffano et al 1984) and, closer to our field of interests, with lesions of the septohippocampal pathways (Emerich 1992). It has been suggested that gangliosides mediate functional recovery by minimizing primary or secondary cell loss or by stimulating regeneration or sprouting of damaged neurons (Sabel 1988, for a comprehensive review).…”
Section: Introductionmentioning
confidence: 99%